Energy Efficiency Labelling: Investigating Students’ Preferences and Awareness on the Energy-efficient Electrical Appliances in Hostel - Kamaludin, Mahirah; Razali, Muhd Azrin Shah; Haron, Nazatul Faizah; Azlina, A. A. (International Journal of Energy Economics and Policy, 2021)
The significant role of energy efficiency labelling should not be ignored as it provides various information that serve as a guideline when people make purchasing decision. It indicates projection energy consumption of an electrical equipment according to energy efficiency rating system. This study applied choice experiment (CE) method in which the conditional logit (CL) model was valued to determine students’ willingness to pay (WTP) based on their preferences of the energy label attributes of table fans. A questionnaire survey was distributed to 151 on-campus students in Terengganu, Malaysia. The attributes were speed of fan, energy consumption and energy star and price of fan. The study found that the students mostly preferred energy consumption attribute with WTP estimation of RM123.538 (USD29.66) at level two and RM42.88 (USD10.30) at level three. These findings illustrate how people place value on monetary and non-monetary attributes based on their preferences. A label with energy-efficient standard makes it easier for utility companies and government energy-conservation organizations to offer consumers incentives to purchase energy-efficient products. The usefulness of energy efficiency label is very reliant in terms of how it portrays information to the people and promote energy conservation. Keywords: Choice Experiment, energy label, energy efficiency, energy conservation, table fan Willingness to Pay. JEL Classifications: D1, Q0, Q4, Q5 DOI: https://doi.org/10.32479/ijeep.10824